License risks from ad hoc reuse of code from the internet. - Sojer, Manuel; Henkel, Joachim (Communications of the ACM, 2011)
The article discusses the reuse of ad hoc code from the Internet, arguing that the use of such code by software developers bears both economic and legal risks for employers. The authors say that Internet code including open source software (OSS), while suitable for reuse in commercial software, is often under licenses which require users to comply with conditions such as obligations under the GNU General Public License (GPL). A survey conducted by the authors found that many software developers do not follow these requirements. The article provides advice on how to mitigate risk by making developers aware of license issues and establishing policies on Internet code.